Mechanizmy zmien dĺzky axónov a dendritov neurónu - Lest'anová, Z; Bacová, Z; Havránek, T; Bakos, J (Ceskoslovenska fysiologie, 2013)
Brain development is determined by neuronal differentiation including changes of cell polarity and asymetric growth of neuronal processes. Although, there are many unkown factors contributing to changes of lenght of neuronal cones, mounting experimental and review papers focus on changes of growth conus and role of axonal transport. In particular, mechanisms of actin/microtubule polymerisation and depolymerisation are important. Role of intracellular calcium is also significant. Normal and properly timed changes of lenght of axons and dendrites are dependent on interaction of neurons and glia. Moreover, regeneration of injured axons is dependent on growth factors secreted from glial cells. The aim of the present study is characterisation of the most important mechanisms underlying changes of lenght of neurites.
Keywords: neurity; dendrity; Microtubules; Neurons; Cell Growth Processes; Neurites; axony; Dendrites; Axons; Actins; Animals; lidé; Humans; buňky - růstové procesy; neurony; zvířata; mikrotubuly; aktiny